Hexavalent (Me ‐ W/Mo)‐modified (Ba, Ca)TiO3‐Bi(Mg, Me)O3 perovskites for high‐temperature dielectrics. Issue 12 (25th August 2020) - Schulz, Thomas; Veerapandiyan, Vignaswaran K.; Gindel, Theresa; Deluca, Marco; Töpfer, Jörg
Abstract: We report on the synthesis of complex lead‐free perovskite‐type (1− x )(Ba0.8 Ca0.2 )TiO3 – x Bi(Mg0.75 W0.25 )O3 (BCT‐ x BMW) and (1− x )(Ba0.8 Ca0.2 )TiO3 ‐ x Bi(Mg0.75 Mo0.25 )O3 (BCT‐ x BMM) solid solutions via conventional solid‐state reaction route. The sintering temperature was adjusted as a function of composition x to obtain dense samples (relative densities over 95%) at the same time minimizing bismuth evaporation. X‐ray diffraction analysis shows the formation of single‐phase perovskites for 0 ≤  x  ≤ 0.10 in the BCT‐ x BMW series and increasing concentrations of impurity phases for x  ≥ 0.15 and for x  ≥ 0.05 in BCT‐ x BMM. A transition from a tetragonal to pseudo‐cubic perovskite structure is observed in BCT‐ x BMW and BCT‐ x BMM at x  = 0.05. The dielectric response has been characterized between −60°C and 300°C for BCT‐ x BMW, and between 30°C and 300°C for BCT‐ x BMM using impedance spectroscopy, showing a transition from ferroelectric to relaxor‐like behavior at x  ≥ 0.05. Additional polarization and Raman spectroscopy measurements reveal the occurrence of highly disordered systems. Analysis of the Raman spectra indicates structural phase changes and lattice modifications caused by chemical substitution. For the composition 0.8Ba0.8 Ca0.2 TiO3 ‐0.2Bi(Mg0.75 W0.25 )O3, a temperature‐stable permittivity of about 600 (±15% between −60°C and 300°C) and small losses of tan δ  < 0.02 for T  ≤ 230°C at 1 kHz are observed, making it a suitable dielectric material for high‐temperature capacitors.